Synthesis of β-triazolylenones via metal-free desulfonylative alkylation of N-tosyl-1,2,3-triazoles - Pati, Soumyaranjan; Almeida, Renata G.; da Silva Júnior, Eufrânio N.; Namboothiri, Irishi N. N. (Beilstein Journal of Organic Chemistry, 2021)
Desulfonylative alkylation of N-tosyl-1,2,3-triazoles under metal-free conditions leading to β-triazolylenones is reported here. The present study encompasses the synthesis of triazoles with a new substitution pattern in a single step from cyclic 1,3-dicarbonyl compounds and N-tosyl triazole in moderate to high yields. Our synthesis takes place with complete regioselectivity as confirmed by crystallographic analysis which is rationalized by a suitable mechanistic proposal. This method provides an efficient, versatile and straightforward strategy towards the synthesis of new functionalized 1,2,3-triazoles.
Keywords: azoles; cycloaddition; enones; heterocycles; 1,2,3-triazoles